The Female Athlete - Hofmann K; Hanke LH; Bjarnason-Wehrens B; Diel PR; Flenker U; Wacker AJ (Deutsche Zeitschrift für Sportmedizin, 2022)
Problem: With menopause, the risk of cardiovascular diseases (CVD) increases significantly. A possible molecular mechanism is an estrogen-related change in fat metabolism. Endurance training has been demonstrated to reduce the risk of CVD and to have an impact on fat metabolism (FM). This study aims to analyze the ability of pre- (preW) and postmenopausal women (postW) of comparable body mass index (BMI) to activate their FM during endurance training.Methods: 12 preW and 12 postW were included. Serum Triglyceride, LDL, HbA1C, estradiol and body composition data were determined. The respiratory quotient (RQ) was determined during moderate 30-minute exercise (60% of the 4 mmol threshold) on an ergometer.Results: While the BMI of preW and postW was comparable, body fat (BF) (p=0.001), lean body mass (LBM) (p=0.001) and abdominal girth (AG) (p=0.003) were significantly different. Significant group effects could also be identified in HbA1c (p=0.001), cholesterol (p=0.001) and LDL (p=0.000) serum concentrations. RQ decreased during 30 minutes of cycling in preW and increased in postW (p=0.010) over time.Discussion: The higher AG and BF and the lower LBM demonstrates the change in body composition in postW. An accumulation of fat, especially in the trunk region, goes along with an increase of CVD in postW, even with a normal BMI.Conclusion: It is evident that postW show altered lipid metabolism compared to preW.Key Words: Menopause, Cardiovascular Risk Factor, Aerobic Training, Metabolism